Validation of the Glicksman Scaling Law for Gas-Solid Conical Fluidized Beds Using the Radioactive Particle Tracking Technique - Kalo L.; Pant H.J.; Upadhyay R.K. (My University, 2025)
In the current work, the scale-up study was performed for gas-solid conical fluidized beds using the radioactive particle tracking technique. Two sets of Glicksman scaling laws were used: The inertial limit set and the simplified set. The hydrodynamic parameters such as mean velocity, root mean square velocity, and granular temperature were calculated from RPT data. Furthermore, the Hurst exponent, autocorrelation functions, Kolmogorov entropy, and correlation dimension were also obtained. The results for all the cases were compared to confirm the equality using both the scaling laws. The results showed that the column, when scaled up using the Glicksman inertial limit set, was able to match most of the flow quantities both qualitatively and quantitatively. The match of the Kolmogorov entropy and correlation dimension for the inertial limit set indicated a dynamic similarity between the two different diameter columns. Hence, the present work recommends the use of the Glicksman inertial limit set for scale-up of the gas-solid conical fluidized bed. ©